Teori Kepimpinan Guru dalam Pendidikan Berasaskan Pemikiran al-Ghazali: Satu Perbandingan dengan Teori Kepimpinan Pendidikan Barat - Mohamad, Ahmad Sukari; Sahad, Mohd Nizam (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
In Islam, every Muslim is a leader and is responsible within the scope of which that has been entrusted to him. In an educational context, teachers are leaders and are responsible in leading and producing the perfect being from the emotional, physical, intellectual and spiritual aspects. However, the responsibility of leading may not be properly implemented if, especially religious teachers, do not orient students towards Islamic leadership, as indicated by the Prophet Muhammad s.a.w. This article aims to discuss teachers’ leadership theory based on the observation of the views and ideas of Islamic education leader, al-Ghazali. The findings towards al-Ghazali’s thinking concerning teachers’ leadership showed that he went beyond his time through his writings related to leadership styles and forms of teachers’ leadership which includes practitioner of parental love, indicator of role model, forming a superior personality, and a leader in teaching and learning. In actual fact, although many western educational leadership theories have been put forward, al-Ghazali’s ideas related to teachers’ leadership are still relevant to be showcased to the world of education at the present time.